Comparative morphology of regenerative inflammatory processes in the skin using peptide activators and preparations based on hyaluronic acid. - Turkevich, M. O.; Turkevich, O. O.; Pospishil, Yu. O. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The rapid development of innovative technologies, particularly in the medicine, requires a continuous update of the arsenal of knowledge and understanding of processes in connection with the introduction of new techniques. Angiogenesis is an extremely important process for the formation of regenerate, since it is the growth of new microvessels that accompanies the migration of cells of the fibroblast row to the site of alteration and provides their metabolic needs. If angiogenesis is stimulated in insufficient amounts, migration of fibroblasts, as well as the processes of regenerationslows down or even stops. The objective of the study was to explore and compare the morphological changes that occur in the dermis at different chronological stages when using peptide activators and preparations based on hyaluronic acid. Methods. The research was conducted on the basis of Danylo Halytsky Lviv National Medical University. For the experiment, 30 adult white rats, 150-180 g were used, which were divided into 3 groups of 10 rats, one of which was administered a peptide activator drug, the other 10 rats were given a hyaluronic acid-based drug, another 10 - control group, which was injected with an isotonic solution of 0.9% NaCl. The rats were removed from the experiment on days 14, 28, and 42 of the study by overdose of diethyl ether, followed by resection of the skin flap from the injection site. Subsequently, hematoxylin-eosin staining, histochemical technique by Malory and immunohistochemical staining using CD34 antibody was performed. Results. It was found that on 42 day of the experiment, there was a slight setback in both cases after a rapid increase in connective tissue volume, in particular collagen at the injection sites. However, angiogenesis stimulated by peptide activators was more active and persistent than in rats administered a hyaluronic acid-based preparation. Conclusion. In the future, it is planned to continue the study of morphological changes in the skin on day 56 in order to confirm the results obtained in the previous stages.